Upaya Pengenalan Pentingnya Pendidikan dan Dampak Pernikahan Dini pada Anak di Rumah Cerdas Anak Perempuan (CAPER) Desa Danau Sijabut - Taufik Hidayat Manurung; Nuri Prasuci; Miwadari Miwadari; Suci Pranasari; Rima Aprilia (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
This article discusses the importance of education, as well as the impact that appears on early marriage. As we know, nowadays there are many cases of early marriage or young marriage. This study uses a correlational description. This research is motivated by the number of early marriages in Lake Sijabut Village due to the lack of education in the village. Early marriage is directly proportional to the high divorce rate because married couples are not ready to build a married life. Psychologically, they are still not mature enough to think, they even tend to be unstable and emotional when problems occur in the household, which ultimately end in divorce. Based on this, it can be concluded that in Lake Sijabut Village early marriage is as follows: 1) Lack of concern for education which is very important; 2) Teenagers who do early marriage still depend on cultural and socioeconomic factors; 3) Lack of supervision and guidance from parents towards children; 4) Lack of education about early marriage in Lake Sijabut Village.